A constructivist approach to promoting spiritual competence in counselor trainees: a pilot study. Issue 1 (2nd January 2022) - Bowser, Devon; Joseph, Matthew; Crothers, Laura M.; Kolbert, Jered B.; Holmes, Imac S.
ABSTRACT: The purpose of this study was to investigate the impact of a two-and-half hour constructivist-oriented training session upon the spirituality and religious competency of 15 master's level counseling students. The results revealed that the master's-lever counselors in training demonstrated a significant overall increase in spiritual and religious competency. Although the intervention resulted in a significant increase in the spiritual and religious competency scores, the participants' scores at posttest remained below the minimum cutoff score, echoing a consistent finding in the literature that counselor preparation programs are not adequately training students to incorporate spirituality and religion in their work. Students who scored higher on a Personal Spiritual and Religious Practices scale demonstrated greater increases in their spiritual competency.